KOMUNIKASI QURANI SEBAGAI RESOLUSI KONFLIK DALAM PERKAWINAN - Jufri Hasani Z; Nurlizam (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
This study aims to reveal the messages of the Qur'an in resolving marital conflicts. Marriage is one of the Shari'a that gets special attention in the Qur'an, one of the forms of attention is to provide a way out in resolving conflicts that occur in marriage. This research method is a qualitative research literature (library research), as for interpreting the verse, the author uses the thematic interpretation method based on the theme. The work step of thematic interpretation that the author uses is the contemporary interpretation step. The results of the study state that in the Qur'an found ways that can be taken in resolving household conflicts, one of which is through a communication approach. Qur'anic communication in resolving household conflicts are: 1) Delivering messages in the best way. 2) Selection of appropriate and accurate message material by considering aspects of Honesty of information and fairness in delivering messages. 3) Verify every information and attitude of responsibility towards the message conveyed, and 4) Discuss wisely and politely.